Analytical analysis for horizontal displacement of pile anchor support structure considering prestress - Ling, Yong-qiang; Song, Lei; Hao, Jian; Cao, Xiao-lin; Yang, Xiao-hui (Frontiers in Ecology and Evolution, 2023)
The pile-anchor supporting structure is widely used in foundation pit engineering, it is particularly necessary for calculating lateral displacement of the pile-anchor supporting structure. The soil stress state is transformed by the additional stress caused by the prestress, thus the lateral displacement can be decreased own to pile-anchor supporting structure bearing active earth pressure had changed. Prestress as a concentrated force is decomposed into the horizontal component and vertical component, calculating the additional stress caused by the prestress and getting the formula of active earth pressure of considering the additional stress, setting up calculation model of the pile-anchor supporting structure. For typical examples of foundation pit engineering, the parameters are substituted into a program written based on derived formulas, and the elastic deformation superposition method is used to calculate the horizontal displacement of the pile anchor support structure. The comparison and verification is carried out by Finite element analysis. The influence of cohesion and friction angle on pile displacement, bending moment, and shear force has been studied. This study found that cohesion and friction angle have a significant impact on the displacement of pile anchor support structures.